DR-CAFTA and the Environment - Cunha, Barbara; Mani, Muthukumara (2012)
The Dominican Republic-Central American Free Trade Agreement with the United States aims to create a free trade zone for economic development. The Agreement is expected to intensify commerce and investment among the participating countries. This paper analyzes the changes in the production and trading patterns in 2-digit manufacturing sectors with the goal of understanding the short-term environmental implications of the Dominican Republic-Central American Free Trade Agreement. More specifically, the paper addresses the questions: Did pollution increase in the period after the Agreement negotiations? Did trade and production shift toward pollution intensive factors? The results suggest an increase in pollution emissions in the post-negotiations period. The increase in emissions is mainly attributable to scale effects. Composition effects are small and in some cases (including Nicaragua and Honduras) favoring cleaner industries and partially compensating the pollution gains from output and export growth.